Long‐term results of the phase II trial of the oral mTOR inhibitor everolimus (RAD001) in relapsed or refractory Waldenstrom Macroglobulinemia. Issue 3 (March 2014) - Ghobrial, Irene M.; Witzig, Thomas E.; Gertz, Morie; LaPlant, Betsy; Hayman, Suzanne; Camoriano, John; Lacy, Martha; Bergsagel, P. Leif; Chuma, Stacey; DeAngelo, Daniel; Treon, Steven P.
<x xml:space="preserve">Abstract</x> Everolimus is an oral raptor mTOR inhibitor and has shown activity in patients with Waldenstrom's macroglobulinemia (WM). This study examines a large cohort of patients with relapsed/refractory WM with long‐term follow up for survival. Patients were eligible if they had measurable disease, a platelet count >75, 000 × 106/L, an absolute neutrophil count >1, 000 × 106/L. Patients received everolimus 10 mg PO daily and were evaluated monthly. A success was defined as a complete or partial response (PR); minor responses (MR) were recorded and considered to be of clinical benefit. Sixty patients were enrolled and treated. The overall response rate (ORR) was 50% (all PR); the clinical benefit rate including MR or better was 73% (95% CI: 60–84%) with 23% MR. The median time to response for patients who achieved PR was 2 months (range, 1–26). The median duration of response has not been reached and median progression‐free survival (PFS) was 21 months. Grade 3 or higher toxicities (at least possibly related to everolimus) were observed in 67% of patients. The most common grade 3 or 4 toxicities were anemia (27%), leukopenia (22%), and thrombocytopenia (20%). Other nonhematological toxicities were diarrhea (5%), fatigue (8%), stomatitis (8%) and pulmonary toxicity (5%). Everolimus has a high single‐agent activity of 73% including MR, with a progression free survival of 21 months, indicating that this agent is active in relapsed/refractory WM. Am. J. Hematol. 89:237–242, 2014. © 2013 Wiley Periodicals, Inc